(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
This paper presents a novel covert channel for secret communications. It implements a new application layer covert channel, by applying multimedia steganography techniques to hide secret messages. This new channel method (called Under Your Radar (UYR)) provides a stealthiness method for the communication channel and an efficient method for hiding messages, as proved by our investigations. Such a covert channel will be used for transferring secret messages in two phases. In phase one, the message characters will be embedded randomly into the pixels of video frames. The choice of pixels is dependent on finding an identical value of the character ASCII representation from one of the pixel channels. The positions of pixels will form the steganography key, which will be used later to extract the message. Also, the steganography key will be embedded in an image using the LSB steganography technique. In phase two, the secret message will be exchanged between the sender and the receiver by sharing the video along with the steganography key over a public service (e.g. a social network), which serves as the new covert communication channel. The experiments outcomes have showed an improvement on the success of the proposed covert channel in exchanging secret messages without rising suspicion by observers or detection tools.